Depression, Anxiety, Insomnia, and Quality of Life in a Representative Community Sample of Older Adults Living at Home - Kennair, Leif Edward Ottesen; Hagen, Roger; Hjemdal, Odin; Havnen, Audun; Ryum, Truls; Solem, Stian (Frontiers in Psychology, 2022)
Background: The aim of the study was to explore symptoms of anxiety and depression, insomnia, and quality of life in a Norwegian community sample of older adults. Methods: A representative sample (N = 1069) was drawn from home-dwelling people of 60 years and above, living in a large municipality in Norway (Trondheim). Results: Based on established cut-off scores, 83.7 % of the participants showed no symptoms of anxiety/depression, 12% had mild symptoms, 2.7% moderate symptoms, 1.5% showed severe symptoms of anxiety/depression. A total of18.4% reported insomnia symptoms. Regarding health-related quality of life, few participants reported problems with self-care, but pain and discomfort were common (59%). Depression/anxiety, insomnia and helath related quality of life showed moderate to strong relationships. Discussion: The results suggest a close interplay between anxiety/depression, insomnia, and health related quality of life in older adults.